2015
DOI: 10.3109/08923973.2015.1009998
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic alcohols in spirits inhibit phagocytosis by human monocytes

Abstract: A large volume of alcoholic beverages containing aliphatic alcohols is consumed worldwide. Previous studies have confirmed the presence of ethanol-induced immunosuppression in heavy drinkers, thereby increasing susceptibility to infectious diseases. However, the aliphatic alcohols contained in alcoholic beverages might also impair immune cell function, thereby contributing to a further decrease in microbicidal activity. Previous research has shown that aliphatic alcohols inhibit phagocytosis by granulocytes bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Some previous research does show that 1‐propanol, 1‐butanol, and 1‐pentanol can be incorporated into the phospholipid bilayer, just like ethanol, thereby altering the membrane fluidity and migration of granulocytes (Tomonaga, Hirota & Snyderman, ; Yuli, Tomonaga & Synderman, ). However, the concentrations of OAAs (9.1–27.3 mM) used in these experiments significantly exceeded the blood levels expected in alcohol abusers (Pál et al, ; Tomonaga, Hirota & Snyderman, ; Yuli, Tomonaga & Synderman, 1982). Consequently, we now ask whether membrane fluidity and migration of granulocytes are affected when cells are treated separately with ethanol, methanol, mixture of OAAs, and mixture of OAAs combined with ethanol at biologically relevant concentrations.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Some previous research does show that 1‐propanol, 1‐butanol, and 1‐pentanol can be incorporated into the phospholipid bilayer, just like ethanol, thereby altering the membrane fluidity and migration of granulocytes (Tomonaga, Hirota & Snyderman, ; Yuli, Tomonaga & Synderman, ). However, the concentrations of OAAs (9.1–27.3 mM) used in these experiments significantly exceeded the blood levels expected in alcohol abusers (Pál et al, ; Tomonaga, Hirota & Snyderman, ; Yuli, Tomonaga & Synderman, 1982). Consequently, we now ask whether membrane fluidity and migration of granulocytes are affected when cells are treated separately with ethanol, methanol, mixture of OAAs, and mixture of OAAs combined with ethanol at biologically relevant concentrations.…”
Section: Introductionmentioning
confidence: 56%
“…Some previous research does show that 1-propanol, 1-butanol, and 1-pentanol can be incorporated into the phospholipid bilayer, just like ethanol, thereby altering the membrane fluidity and migration of granulocytes (Tomonaga, Hirota & Snyderman, 1983;Yuli, Tomonaga & Synderman, 1982). However, the concentrations of OAAs (9.1-27.3 mM) used in these experiments significantly exceeded the blood levels expected in alcohol abusers (Pál et al, 2015;Tomonaga, Hirota & Snyderman, 1983;Yuli, Tomonaga & Synderman, 1982).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…We have previously shown that AAs can decrease superoxideanion production by human granulocytes and inhibit phagocytosis by human granulocytes and monocytes in a concentration dependent manner and, when combined with ethanol, they caused a further decrease in phagocytic activity (22)(23)(24). We have found similar effects when granulocytes and monocytes were exposed to metabolites of AAs including formaldehyde, 1-propanal, acetone, 1-butanal, and 2-butanone (25).…”
Section: Short-chain Alcohols Upregulate Gilz Gene Expression and Attmentioning
confidence: 64%
“…We have found similar effects when granulocytes and monocytes were exposed to metabolites of AAs including formaldehyde, 1-propanal, acetone, 1-butanal, and 2-butanone (25). We have also calculated that blood concentrations of AAs and their metabolites could reach levels sufficient to decrease phagocytosis by granulocytes and monocytes in a clinically meaningful way in heavy users of distilled spirits (24,25). Thus, AAs and their metabolites may contribute to increased susceptibility to infectious diseases (22)(23)(24)(25).…”
Section: Short-chain Alcohols Upregulate Gilz Gene Expression and Attmentioning
confidence: 67%